Polypropylene/Pt Nanocomposite: Synthesis, Characterization and Study the Cytotoxic Effects - Mohammed Abdulwahid A.; Abbass, Nada (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This paper presents the synthesis of a polypropylene nanocomposite. The nanocomposites were characterized using different techniques: atomic electron microscopy (AFM), surface shape was evaluated by (SEM),(EDS),(XRD) and (FTIR). The study showed that the platinum nanocomposite had a fatal effect on both strains of bacteria used, as well as on the growth of fungi. The compound tested showed antioxidant properties moderate activity was found. The mentioned material were evaluated in normal cell line HdFn (Human Dermal Fibroblasts, neonatal) and breast cancer MCF-7 cancer cell line , by MTT assay for study cytotoxic effects, morphological changes, all experiments were conducted on cell lines by using the materials alone. The results of the MTT assay showed that the material [PP/ Pt] had a toxic effect on the cell lines, and the toxicity of the materials was concentration-dependent manner where that have higher toxicity on the MCF-7 cell lines than HdFn. The toxic effects of material alone were reflected on cell morphology by appearance irreversible cytopathic changes in the treated cells, which ability to cause cellular death and DNA damage. When there appeared a significant increase in the concentration of nanocomposite , [PP/Pt] nanocomposite have an inhibitory effect on both breast cancer and normal cell lines. Conclude both materials have genotoxic effects on normal and cancer cell lines.